Aluminum alloy foil
By controlling the proportion of silicon and magnesium content in aluminum alloy foil and optimizing its grain size and crystal orientation, the problems of insufficient ductility of existing aluminum alloy foil and delamination caused by magnesium are solved, and high ductility and strength in all directions are achieved.
Patent Information
- Application Number
- JP2023150804
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-19
- Publication Date
- 2025-04-01
AI Technical Summary
In the packaging materials of existing aluminum alloy foils, such as food and lithium-ion batteries, there is insufficient ductility, especially in the 45° and 90° directions, and the magnesium content will cause delamination and affect the performance of the foil.
By controlling the content ratio of silicon (Si) and magnesium (Mg), the grain size and crystal orientation of aluminum alloy foil are optimized to ensure high ductility in the rolling direction, 45° and 90° directions, while avoiding delamination problems caused by magnesium.
The high ductility and strength of aluminum alloy foil in all directions is achieved, ensuring its excellent shape memory performance and durability in packaging materials.
Smart Images

Figure 2025043496000001 
Figure 2025043496000002 
Figure 2025043496000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to aluminum alloy foils. [Background technology]
[0002] Aluminum alloy foils used as packaging materials for foods, lithium-ion batteries, etc. are required to have excellent formability because they are formed by applying large deformations by press forming, etc. In order to achieve excellent formability in aluminum alloy foils, it is considered important that the crystal grains are fine and uniform, and that the texture is random.
[0003] For example, Patent Document 1 discloses an aluminum foil having a predetermined chemical composition, a volume fraction of a cube texture of 5-20% (preferably 8-15%, more preferably 9-14%), and an average surface grain size of 5-35 μm (preferably 10-20 μm, more preferably 12-18 μm). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2022-047475 Summary of the Invention [Problem to be solved by the invention]
[0005] The present disclosure has been made in consideration of the above-mentioned circumstances, and has an object to provide an aluminum alloy foil having excellent formability. [Means for solving the problem]
[0006] In the manufacture of aluminum alloy foils used as packaging materials for food, lithium ion batteries, etc., so-called stretch forming is often performed, rather than simply stretching in one direction. For this reason, high elongation is required not only in the direction parallel to the rolling direction, which is used as the elongation value of general materials, but also in each direction such as the 45° direction and the 90° direction. The above-mentioned Patent Document 1 does not take into account the elongation in each direction.
[0007] In the aluminum alloy foil used in the above-mentioned packaging material, the inclusion of Mg has been avoided because it causes delamination. Therefore, the properties of the aluminum alloy foil containing Mg have not been fully investigated. As a result of the inventors' investigation into the properties of the aluminum alloy foil containing Mg, the inventors have obtained the following findings.
[0008] The inventors have found that by adding a small amount of Mg to an aluminum alloy foil and controlling the ratio of the Si content to the Mg content, it is possible to refine the crystal grains and develop the Cu orientation. The inventors have found that these actions result in high elongation not only in the rolling direction but also in the 45° and 90° directions.
[0009] The gist of the present disclosure made based on the above findings is as follows. (1) Chemical composition, in mass%, Si: 0.17% or less, Fe: 1.00-1.80%, Cu: 0.004 to 0.015%, and Mg: 0.0010 to 0.0300% The balance is Al and impurities. The ratio of the Si content to the Mg content, Si / Mg, is 150 or less, The average crystal grain size is 35 μm or less, An aluminum alloy foil having a cube orientation density of 10.0 or less and a copper orientation density of 15.0 or more. (2) The elongation rate in the 0° direction, the 45° direction, and the 90° direction relative to the rolling direction is 20.0% or more, The value obtained by subtracting the elongation in the 0° direction from the elongation in the 45° direction is 3.0% or more, The aluminum alloy foil according to (1) above, characterized in that the minimum value of 0.2% yield strength in each of the 0° direction, 45° direction and 90° direction with respect to the rolling direction is 28 MPa or more. (3) The aluminum alloy foil according to (1) or (2) above, characterized in that the maximum protruding height is 5.0 mm or more. Effect of the Invention
[0010] According to the present disclosure, an aluminum alloy foil having excellent formability can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an aluminum alloy foil according to an embodiment of the present disclosure will be described in detail. However, the present disclosure is not limited to the configuration disclosed in the present embodiment, and various modifications are possible without departing from the spirit of the present disclosure.
[0012] Each of the constituent elements of the present disclosure will be described in detail below. First, the reasons for limiting the chemical composition of the aluminum alloy foil according to the present embodiment will be described. In the following, the numerical ranges described with "~" include the lower and upper limits. Numerical values indicated as "less than" or "greater than" are not included in the numerical range. In the following description, % for chemical composition is mass % unless otherwise specified.
[0013] The aluminum alloy foil according to this embodiment has a chemical composition, in mass%, of Si: 0.17% or less, Fe: 1.00 to 1.80%, Cu: 0.004 to 0.015%, and Mg: 0.0010 to 0.0300%, with the remainder being Al and impurities. The ratio of the Si content to the Mg content, Si / Mg, is 150 or less. Each element will be described below.
[0014] Si:0.17% or less Si is an element that forms intermetallic compounds together with Fe. If the Si content exceeds 0.17%, coarse intermetallic compounds are generated. The coarse intermetallic compounds cause deterioration of rollability, reduction in elongation, and coarsening of recrystallized grains (crystal grains after final annealing). Therefore, the Si content is set to 0.17% or less. The Si content is preferably 0.15% or less. The lower limit of the Si content is not particularly limited, but it may be 0% or may be 0.01% or more.
[0015] Fe: 1.00-1.80% Fe is an element that crystallizes as an Al-Fe intermetallic compound during casting. When the size of the Al-Fe intermetallic compound is large, it becomes a recrystallization site during final annealing, and the recrystallized grains are refined. If the Fe content is less than 1.00%, the distribution density of the coarse Al-Fe intermetallic compounds becomes low, and the recrystallized grains cannot be sufficiently refined. Therefore, the Fe content is set to 1.00% or more. The Fe content is preferably 1.20% or more. On the other hand, if the Fe content exceeds 1.80%, the effect of refining the recrystallized grains is saturated or reduced. In addition, the size of the Al-Fe intermetallic compounds formed during casting becomes very large, which deteriorates the formability and rollability of the aluminum alloy foil. Therefore, the Fe content is set to 1.80% or less. The Fe content is preferably 1.60% or less.
[0016] Cu: 0.004~0.015% Cu is an element that increases the strength of aluminum alloy foil and reduces elongation. It is also known that Fe has an effect of suppressing excessive work softening during cold rolling in Al-Fe alloys. If the Cu content is less than 0.004%, the effect of suppressing work softening is reduced, and formability is significantly deteriorated. Therefore, the Cu content is set to 0.004% or more. The Cu content is preferably 0.006% or more. In addition, if the Cu content exceeds 0.15%, the hardness of the aluminum alloy foil increases, and the formability significantly deteriorates. Therefore, the Cu content is set to 0.015% or more. The Cu content is preferably 0.013% or less.
[0017] Mg: 0.0010~0.0300% Mg is an element that has been avoided in aluminum alloy foils used in packaging materials for food, lithium ion batteries, etc., because it causes delamination. Mg is known as an element that dissolves in aluminum to increase strength and reduce elongation. However, in the present disclosure, the effect of recrystallization grain refinement is obtained by closely and inseparably controlling the Mg content and the ratio of the Si content to the Mg content. If the Mg content is less than 0.0010%, the recrystallization grains cannot be refined sufficiently. Therefore, the Mg content is set to 0.0010% or more. The Mg content is preferably 0.0020% or more. Moreover, if the Mg content exceeds 0.0300%, the recrystallized grains cannot be sufficiently refined, so the Mg content is set to 0.0300% or less, and preferably to 0.0100% or less. Most of Mg is dissolved in the matrix, and a part of it is concentrated in the surface layer portion of the aluminum alloy foil during final annealing. However, the presence of the Mg-enriched surface layer portion does not affect the average crystal grain size or mechanical properties.
[0018] The ratio of Si content to Mg content (Si / Mg): 150 or less If the Si / Mg ratio exceeds 150, the recrystallized grains cannot be sufficiently refined, and the formability of the aluminum alloy foil deteriorates. Therefore, the Si / Mg ratio is set to 150 or less. The Si / Mg ratio is preferably 100 or less. The lower limit of Si / Mg is not particularly limited, but may be 0 or more, or 2 or more.
[0019] Remainder: Al and impurities The aluminum alloy foil according to the present embodiment has the above-mentioned chemical composition, with the balance being Al and impurities. In the present embodiment, the impurities refer to substances that are mixed in from raw materials or the manufacturing environment when manufacturing the aluminum alloy foil, and / or substances that are allowed within a range that does not adversely affect the aluminum alloy foil according to the present embodiment.
[0020] The chemical composition of the aluminum alloy foil is analyzed using a spark discharge optical emission spectrometer after a sample of molten aluminum solidified in a Pechini mold during casting has been cut off to a thickness of 3 mm or more from the measurement surface.
[0021] Average grain size: 35μm or less By miniaturizing the crystal grain size (average crystal grain size) in the aluminum alloy foil, it is possible to suppress surface roughness during deformation. As a result, it is possible to increase elongation and obtain excellent formability. If the average crystal grain size exceeds 35 μm, it is not possible to suppress surface roughness during deformation, and formability is deteriorated. Therefore, the average crystal grain size is set to 35 μm or less. The average crystal grain size is preferably 30 μm or less. There is no particular lower limit for the average crystal grain size, but it may be 5 μm or more.
[0022] The crystal grain size of the aluminum alloy foil is measured by the following method. After electrolytically polishing the surface of the aluminum alloy foil, crystal orientation analysis is performed by measuring three fields of view of 45 μm × 90 μm at 1000x magnification using SEM-EBSD analysis equipment consisting of a scanning electron microscope and an EBSD detector. Areas surrounded by boundaries with an orientation difference of 15° or more are considered to be crystal grains, and the circle equivalent diameter of the crystal grains is obtained using the Area method. The average value of the measurements obtained for the three fields of view is calculated to obtain the average crystal grain size.
[0023] The detailed measurement and analysis conditions for SEM-EBSD are as follows: (Measurement conditions) SEM: JEOL JSM-7900F Observation magnification: 1000x Acceleration voltage: 15 kV Sample tilt angle: 70° Step Size: 0.5μm (Analysis conditions) Analysis software: TSL Solutions' OIM Analysis (Ver.8.0) Area: 12,000μm2 in total, obtained by connecting three images taken at 1000x magnification 2 End CI value (Confidence Index): Exclude values below 0.1 Minimum Grain Size[points]:2 pixel Anti Grains:2
[0024] The conditions for measuring the crystal grain size are as follows. Grain Tolerance Angle: 15° Minimum Grain Size[points]:2 pixel Anti Grains:2 pixel Minimum Confidence Index: 0.1 Multiple rows required: All OFF Apply partition before calculation:OFF Include grains at edges of scan in statistics:OFF
[0025] Cube orientation density: 10.0 or less, Cu orientation density: 15.0 or more The texture of aluminum alloy foil is a factor that has a large effect on elongation. If the Cube orientation density is more than 10.0 or the Cu orientation density is less than 15.0, the elongation in the 45° direction to the rolling direction decreases, or the value obtained by subtracting the elongation in the rolling direction from the elongation in the 45° direction to the rolling direction decreases, resulting in poor formability. Therefore, the Cube orientation density is set to 10.0 or less, and the Cu orientation density is set to 15.0 or more. The Cube orientation density is preferably 8.0 or less. The lower limit of the Cube orientation density is not particularly limited, but may be 1.0 or more. The Cu orientation density is preferably 20.0 or more. The upper limit of the Cu orientation density is not particularly limited, but may be 50.0 or less.
[0026] The cube orientation density and the Cu orientation density are measured by the following method. Cube orientation is {001} <100> is the representative orientation, and the Cu orientation is {112} <111> was set as the representative orientation. <100> is regarded as the Cube direction, {112} <111> is regarded as the Cu orientation. In the X-ray diffraction method, the incomplete pole figures of {200}, {220}, and {111} are measured, and the Cube orientation density and Cu orientation density are obtained by calculating the three-dimensional orientation distribution function (ODF) using the obtained results.
[0027] Elongation rate in the 0° direction, 45° direction, and 90° direction relative to the rolling direction: all 20.0% or more In order to achieve excellent formability, it is important that the aluminum alloy foil has high elongation. In particular, it is important that the aluminum alloy foil has high elongation in each direction, 0° direction, 45° direction, and 90° direction, which is the normal direction to the rolling direction, with the direction parallel to the rolling direction being the 0° direction. If the elongation in any direction is 20.0% or more, it can be determined that the aluminum alloy foil has excellent formability. Therefore, it is preferable that the aluminum alloy foil according to this embodiment has elongation in the 0° direction, the 45° direction, and the 90° direction with respect to the rolling direction be 20.0% or more.
[0028] Elongation at 45° to the rolling direction minus elongation at 0°: 3.0% or more Since the elongation rate in the 45° direction to the rolling direction is higher than the elongation rate in the rolling direction (0° direction to the rolling direction), the bulging height during bulging increases. To reliably obtain this effect, it is preferable that the value obtained by subtracting the elongation rate in the 0° direction from the elongation rate in the 45° direction to the rolling direction is 3.0% or more.
[0029] Minimum 0.2% yield strength in the 0°, 45° and 90° directions relative to the rolling direction: 28MPa or more When the aluminum alloy foil is used as a packaging material, it is necessary that the aluminum alloy foil has a certain degree of strength to prevent wrinkles. If the 0.2% proof stress in the 0°, 45°, and 90° directions relative to the rolling direction is 28 MPa or more, the aluminum alloy foil is unlikely to cause problems when used as a packaging material and has an excellent balance between elongation and strength. Therefore, the minimum value of the 0.2% proof stress in the 0°, 45°, and 90° directions relative to the rolling direction is preferably 28 MPa or more. The minimum value of the 0.2% proof stress in the 0°, 45°, and 90° directions is preferably 31 MPa or more.
[0030] The elongation and 0.2% yield strength are measured by the following methods. Conduct tensile tests in accordance with JIS Z 2241:2022. A JIS No. 5 test piece is taken from the aluminum alloy foil so that the elongation can be measured in the 0°, 45°, and 90° directions relative to the rolling direction. A tensile test is performed on the taken test piece using a universal tensile tester (Shimadzu Corporation, AGS-X 10kN) at a tensile speed of 2mm / min to obtain the elongation percentage and 0.2% yield strength. The elongation percentage is calculated as follows. First, before the tensile test, two lines are drawn perpendicular to the test piece at the center position in the longitudinal direction of the test piece, spaced 50 mm apart (the gauge length). After the tensile test, the fracture surfaces of the test piece are butted together to measure the distance between the two lines, and the elongation amount (mm) is obtained by subtracting the gauge length (50 mm) from the measured value. The elongation amount (mm) obtained is divided by the gauge length (50 mm) to obtain the elongation percentage (%). The elongation percentage here refers to the total elongation at break as defined in JIS Z 2241:2022.
[0031] The rolling direction of the aluminum alloy foil is determined based on the coil end, and the direction parallel to the coil end is regarded as the rolling direction.
[0032] Maximum overhang height: 5.0mm or more As an index of stretch formability, the maximum stretch height measured by an Erichsen tester is effective. In the aluminum alloy foil according to the present embodiment, in order to improve the stretch formability, the maximum stretch height is preferably set to 5.0 mm or more.
[0033] The maximum overhang height is measured by the following method. An Erichsen test is performed using a universal sheet metal forming tester (ERICHSEN Model 142 / 20). For the Erichsen test, a metal ball-head punch with a radius of 10 mm is used, and mineral oil is applied to the surface of the aluminum alloy foil that comes into contact with the punch for lubrication. The aluminum alloy foil is fixed to the device with a wrinkle suppression force of 10 kN, and stretch forming is performed with the punch rising speed of 2.8 mm / min. The maximum stretch height is obtained by determining the forming height at which cracks appear in the aluminum alloy foil.
[0034] The thickness of the aluminum alloy foil according to the present embodiment is preferably, for example, 0.030 mm to 0.080 mm, and the thickness of the aluminum alloy foil is a general thickness for use as a foil. The elongation rate and maximum protrusion height vary depending on the thickness of the aluminum alloy foil, but if it is within the above-mentioned range of 0.030 to 0.080 mm, the elongation rate and maximum protrusion height desired in this embodiment can be realized.
[0035] Next, a preferred method for producing the aluminum alloy foil according to this embodiment will be described. A preferred method for producing the aluminum alloy foil according to this embodiment is as follows: obtaining an ingot having the above-mentioned chemical composition; A process of performing homogenization treatment at a temperature range of 480 to 540 ° C for 6 hours or more; A process of hot rolling so that the finishing temperature is in the range of 230 to 300 ° C.; A step of cold rolling so that the final rolling ratio is 85.0 to 99.5%; and a final annealing step in which the steel sheet is held in a temperature range of 200 to 330°C for 10 hours or more.
[0036] The method for producing an ingot having the above-mentioned chemical composition is not particularly limited as long as the chemical composition is within the above-mentioned range, and the ingot may be produced by, for example, continuous casting.
[0037] Homogenization: Maintain temperature range of 480-540℃ for 6 hours or more The obtained ingot is preferably subjected to homogenization treatment by holding for 6 hours or more in a temperature range of 480 to 540° C. If the homogenization temperature is less than 480° C., the crystal grain size becomes small and the desired texture may not be obtained. On the other hand, if the homogenization temperature exceeds 540° C., intermetallic compounds may grow significantly, resulting in coarsening of crystal grains, and the texture may not be controlled to a desired state. In order to precipitate fine intermetallic compounds at a high density in the homogenization treatment in which the temperature is maintained in the range of 480 to 540°C, a long heat treatment is required. Therefore, the holding time of the homogenization treatment is preferably 6 hours or more. If the holding time is less than 6 hours, fine intermetallic compounds cannot be sufficiently precipitated, and the texture cannot be preferably controlled.
[0038] Hot rolling finishing temperature: 230~300℃ In hot rolling, it is preferable to suppress recrystallization by setting the finishing temperature (final stage delivery temperature) to 300°C or less. By setting the finishing temperature of hot rolling to 300°C or less, the structure of the hot rolled sheet can be made into a uniform fibrous structure. By suppressing recrystallization after hot rolling in this way, the amount of strain accumulated until the subsequent final annealing is increased, and a recrystallized structure with a uniform grain size can be obtained after the final annealing. If the finishing temperature is more than 300°C, recrystallization occurs in a part of the hot rolled sheet, resulting in a mixture of fibrous structure and recrystallized grain structure. This may result in coarsening of the recrystallized grain size after the final annealing. In order to make the finishing temperature less than 230°C, the temperature during hot rolling must also be extremely low. If the temperature during root rolling is low, cracks may occur on the sides of the hot-rolled sheet, resulting in a significant drop in productivity. Therefore, it is preferable to make the finishing temperature 230°C or higher.
[0039] Final reduction rate of cold rolling: 85.0~99.5% The higher the final reduction ratio of cold rolling, the more strain is accumulated in the cold rolled sheet, the finer the recrystallized grains are after final annealing, and the Cu orientation develops significantly. If the final reduction ratio of cold rolling is too low, it causes the recrystallized grains to become coarse and non-uniform. Therefore, the final reduction ratio of cold rolling is preferably 85.0% or more. On the other hand, if the final cold rolling reduction exceeds 99.5%, work hardening is promoted and breakage during cold rolling is likely to occur, so the final cold rolling reduction is preferably 99.5% or less.
[0040] The final rolling reduction ratio of cold rolling can be expressed as (t0-t1) / t0×100(%), where t0 is the thickness before the final stage of cold rolling and t1 is the thickness after the final stage of rolling.
[0041] Final annealing: 10 hours or more at a temperature range of 200 to 330°C The aluminum alloy foil is softened by performing final annealing after cold rolling. If the temperature of the final annealing is less than 200°C or the holding time is less than 10 hours, the foil may not be sufficiently softened and the texture may not be favorably controlled. Therefore, it is preferable that the temperature of the final annealing is 200°C or higher and the holding time is 10 hours or more. On the other hand, if the temperature of the final annealing exceeds 330° C., problems such as deformation of the aluminum alloy foil and reduced economic efficiency arise. Therefore, the temperature of the final annealing is preferably 330° C. or less. The upper limit of the holding time is more preferably less than 150 hours from the viewpoint of economic efficiency.
[0042] Intermediate annealing Intermediate annealing may be performed between multiple cold rolling passes. Intermediate annealing is an optional step and may or may not be performed. When intermediate annealing is performed, it is preferable to heat the steel sheet to a temperature range of 200 to 400°C for several tens of minutes to several hours. For example, it is preferable to heat the steel sheet to a temperature range of 320 to 380°C for 3 hours and then slowly cool the steel sheet. EXAMPLES
[0043] Next, the effect of one embodiment of the present disclosure will be described in more detail with reference to an example, but the conditions in the example are one example of conditions adopted to confirm the feasibility and effect of the present disclosure, and the present disclosure is not limited to this one example of conditions. Various conditions may be adopted in the present disclosure as long as they do not deviate from the gist of the present disclosure and the object of the present disclosure is achieved.
[0044] Aluminum alloy foils having the chemical compositions shown in Tables 1A and 1B were produced under the production conditions shown in Tables 1A and 1B. The thickness of each of the obtained aluminum alloy foils was 0.040 mm. In some cases, intermediate annealing was performed by holding the steel sheet in a temperature range of 350 to 370° C. for 3 hours.
[0045] For the obtained aluminum alloy foil, the average crystal grain size, Cube orientation density, Cu orientation density, elongation (EL) and 0.2% yield strength in the 0°, 45° and 90° directions relative to the rolling direction, and maximum protrusion height were determined by the above-mentioned methods.
[0046] The results obtained are shown in Tables 2A and 2B. When all of the following criteria were satisfied for each mechanical property, the aluminum alloy foil was judged to be acceptable as having excellent formability. On the other hand, when one or more of the following criteria were not satisfied, the aluminum alloy foil was judged to have no excellent formability and was rejected. Note that Nos. 26 and 27 were not suitable for use as products because of insufficient softening and poor formability, and the texture could not be favorably controlled.
[0047] Elongation rate in the 0° direction, 45° direction, and 90° direction relative to the rolling direction: all 20.0% or more Elongation at 45° to the rolling direction minus elongation at 0°: 3.0% or more Minimum 0.2% yield strength in the 0°, 45° and 90° directions relative to the rolling direction: 28MPa or more Maximum overhang height: 5.0mm or more
[0048] [Table 1A]
[0049] [Table 1B]
[0050] [Table 2A]
[0051] [Table 2B]
[0052] As can be seen from Tables 2A and 2B, the aluminum alloy foil according to the present disclosure has excellent formability. [Industrial Applicability]
[0053] According to the present disclosure, an aluminum alloy foil having excellent formability can be provided.
Claims
1. The chemical composition, in mass%, is Si: 0.17% or less, Fe: 1.00-1.80%, Cu: 0.004 to 0.015%, and Mg: 0.0010 to 0.0300%; The balance is Al and impurities. The ratio of the Si content to the Mg content, Si / Mg, is 150 or less; The average crystal grain size is 35 μm or less, An aluminum alloy foil having a Cube orientation density of 10.0 or less and a Cu orientation density of 15.0 or more.
2. The elongation rate in the 0° direction, the elongation rate in the 45° direction, and the elongation rate in the 90° direction relative to the rolling direction are 20.0% or more, The value obtained by subtracting the elongation in the 0° direction from the elongation in the 45° direction is 3.0% or more, 2. The aluminum alloy foil according to claim 1, wherein the minimum value of 0.2% proof stress in each of the 0° direction, the 45° direction, and the 90° direction with respect to the rolling direction is 28 MPa or more.
3. 3. The aluminum alloy foil according to claim 1, wherein the maximum protruding height is 5.0 mm or more.
Citation Information
Patent Citations
Aluminum foil, method for producing the same and use thereof
JP2022047475A